The Integration of Digital Learning Media in Islamic Religious Education: A Study on Management and Implementation at Bumrungsuksa Islamic Boarding School, Thailand - Setiawan, Hasrian Rudi; Syaukani, Syaukani; Audia, Rindi Irma; Hawaree, Hawaree (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the management and implementation of digital learning media in Islamic Religious Education at Bumrungsuksa Islamic Boarding School, Thailand. The research focuses on understanding how digital learning media is integrated into the teaching process, the challenges encountered, and the effectiveness of its application in improving students’ learning experiences. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews. The quantitative data is gathered through structured questionnaires distributed to teachers and students, while qualitative insights are obtained from in-depth interviews with school administrators and educators. Additionally, classroom observations are conducted to assess the practical implementation of digital learning media. The findings indicate that the integration of digital learning media has positively impacted students’ engagement and comprehension in Islamic Religious Education. However, challenges such as limited digital infrastructure, teacher readiness, and access to suitable digital content remain significant concerns. The study highlights the importance of strategic management in ensuring the effective use of digital learning media, including teacher training, resource allocation, and policy development. The results suggest that a well-structured management system can enhance the effectiveness of digital learning media, making Islamic Religious Education more interactive and accessible.